Targets for therapy in sarcomeric cardiomyopathies. (29th January 2015) - Tardiff, Jil C.; Carrier, Lucie; Bers, Donald M.; Poggesi, Corrado; Ferrantini, Cecilia; Coppini, Raffaele; Maier, Lars S.; Ashrafian, Houman; Huke, Sabine; van der Velden, Jolanda
Abstract: To date, no compounds or interventions exist that treat or prevent sarcomeric cardiomyopathies. Established therapies currently improve the outcome, but novel therapies may be able to more fundamentally affect the disease process and course. Investigations of the pathomechanisms are generating molecular insights that can be useful for the design of novel specific drugs suitable for clinical use. As perturbations in the heart are stage-specific, proper timing of drug treatment is essential to prevent initiation and progression of cardiac disease in mutation carrier individuals. In this review, we emphasize potential novel therapies which may prevent, delay, or even reverse hypertrophic cardiomyopathy caused by sarcomeric gene mutations. These include corrections of genetic defects, altered sarcomere function, perturbations in intracellular ion homeostasis, and impaired myocardial energetics.